2009
DOI: 10.1080/10739680802462792
|View full text |Cite
|
Sign up to set email alerts
|

Event‐Tracking Model of Adhesion Identifies Load‐Bearing Bonds in Rolling Leukocytes

Abstract: Objectives P-selectin binding to P-selectin glycoprotein ligand (PSGL)-1 mediates leukocyte rolling under conditions of inflammation and injury. The objectives were to develop an efficient, high temporal resolution model for direct simulation of leukocyte rolling, and then to conduct a study of load-bearing bonds using the model. Methods A stochastic π-calculus-driven Event Tracking Model of Adhesion was developed and compared with experimental data. Multiple simulations for each case were conducted to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…The proposed model is in good agreement with the experimental data of Shao et al 29. Using a modified version of our Event-Tracking Model of Adhesion (ETMA)23, we conducted multiple simulations of neutrophil rolling. By directly comparing the microvillus deformation process with the lifetimes of load-bearing bonds of that microvillus, we demonstrate how P-selectin—PSGL-1 load-bearing bonds shape microvillus deformation during neutrophil rolling.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The proposed model is in good agreement with the experimental data of Shao et al 29. Using a modified version of our Event-Tracking Model of Adhesion (ETMA)23, we conducted multiple simulations of neutrophil rolling. By directly comparing the microvillus deformation process with the lifetimes of load-bearing bonds of that microvillus, we demonstrate how P-selectin—PSGL-1 load-bearing bonds shape microvillus deformation during neutrophil rolling.…”
Section: Introductionsupporting
confidence: 75%
“…The PSGL-1 molecules are present on the microvilli tips(Figure 1). 5 Most newly created P-selectin—PSGL-1 bonds bear no load initially, and some dissociate before becoming load bearing 23. Because of the cell’s motion, bonds can become load bearing (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The force dependence of HuEP-P-selectin bond lifetimes as modeled by the Bell equation38 suggested that the reactive compliance of the antibody-antigen bond, and therefore its intrinsic affinity, was unaffected by the PEG spacers and immobilization strategies. How bond length could influence bond lifetime can be explained in part by analogy to how extensible microvilli strengthen leukocyte rolling on P-selectin 26, 49, 50. In brief, the longer bond structure allows the bond to preferentially localize at the trailing edge of the moving leukocyte, or microparticle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, P-selectin Glycoprotein Ligand-1 (PSGL-1), the main leukocyte ligand for P-selectin, is a constitutive dimer, 3 and the dimers are clustered on the tips of leukocyte microvilli. 4 The rolling is insensitive to reasonable changes in the number 5 and distribution 6 of microvilli on the cell surface.…”
Section: Cd63 Positions Cd62p For Rolling ---------------------------mentioning
confidence: 99%
“…Efforts to model leukocyte rolling 5,11,12 have assumed randomly distributed P-selectin, which clearly does not capture the biologic situation on endothelial cells. Pselectin is clustered, and this clustering requires CD63.…”
Section: 3 O C T O B E R 2 0 1 1 I V O L U M E 1 1 8 N U M B E R mentioning
confidence: 99%